Pengaruh Disiplin, Motivasi Belajar, Keterampilan Mengajar Guru, Media Pembelajaran terhadap Minat Belajar Siswa Kelas XII AKL SMK Negeri 2 Bukittinggi pada Pembelajaran Jarak Jauh di Era New Normal - Illya Fira; Ansofino Ansofino; Nora Susanti (STKIP PGRI Sumatera Barat, 2021)
This study aims to analyze: 1.) The effect of learning discipline on interest in learning 2.) The effect of learning motivation on interest in learning 3.) The effect of teacher teaching skills on interest in learning 4.) The effect of learning media on interest in learning 5.) To analyze learning discipline , learning motivation, teacher teaching skills and learning media simultaneously on online learning outcomes in economics class XII AKL SMK Negeri 2 Bukittinggi. The population of this study were students of class XII AKL SMK Negeri 2 Bukittinggi, amounting to 90 people. The sampling technique used was Stratified Sampling with a total sample of 62 people. The instrument used for this research is a closed questionnaire using the Multilevel Linear Regression test and hypothesis testing with t test and F test.The results of the study show that: (1) learning discipline greatly affects students' interest in learning, a greater influence is found in the sample group of non-current internet network ownership, this is because if internet access is inadequate it will affect students' interest in learning; (2) learning motivation greatly affects students' interest in learning, the biggest influence comes from students with poor internet access this is due to the lack of student motivation in distance learning because the network is less stable this affects interest in learning; (3) teacher's teaching skills greatly affect interest in learning, the greater influence comes from samples with ownership of internet access that is not smooth, this is because if internet access is lacking, the learning process changes from conventional to network that still does not master technology so that the learning process does not run. maximum ; (4) learning media greatly influences interest in learning, the biggest influence comes from samples of internet access that are not smooth, this is because not all students have internet access and difficulties in using the learning media provided, so that it will affect students' interest in learning.